Analysis Marketing of Goat Milk at Tharraya Farm, Sunggal Subdistrict - Indri Safira Lubis; Galih Ari Wirawan Siregar (Talenta Publisher, 2025)
This study aims to determine the characteristics of the marketing institutions involved in marketing goat milk, determine the channel shape and function of marketing goat milk, determine the cost of marketing margins, farmer's share, and profit ratios marketing goat milk as well as analyze the marketing efficiency of goat milk at Tharaya Farm District Sunggal. The method used in data collection is purposive sampling. Primary data was collected through interviews using questionnaires and direct observation of breeders, intermediary traders and consumers. The parameters studied were marketing institutions, marketing channels, marketing margins, farmer's share, profit to cost ratio. The results of this study indicate that the marketing agencies involved in marketing goat milk at Tharraya Farm are breeders and retailers. There are two milk marketing channels at Tharraya Farm, namely, Channel I: Breeder-Consumer, Channel II: Breeder-Retailer-Consumer. Based on the marketing analysis, the margin share was obtained, where in this analysis channel I (Rp. 30,600) was greater than channel II (Rp. 0). Farmer's Share Channel II (100%) is greater than channel I (60%). The profit ratio of channel I (11.17) is smaller than channel II (15.4). The efficiency of the milk marketing channel at Tharraya Farm can be seen from its marketing efficiency, that each marketing channel is efficient with a value between 0-33%. The conclusion of this research is the marketing of goat milk at Tharraya Farm has been efficient.